1991
DOI: 10.3109/00016489109137409
|View full text |Cite
|
Sign up to set email alerts
|

Histo-anatomical Structure of the Human Laryngeal Ventricle

Abstract: A study of the microstructure of the human laryngeal ventricle and ventricular band was carried out on 20 human larynges in an attempt to up-date and elucidate the function of these structures. Celloidin and paraffin whole organ coronal serial sections were studied to clarify the epithelial, glandular as well as muscular structures of the ventricle and ventricular band. The present study showed that the superior thyro-arytenoid muscle was bilaterally present in 80% of cases. On the other hand, the ventriculari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
24
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 3 publications
10
24
0
Order By: Relevance
“…The position of these fibers roughly corresponds to fibers identified as thryoepiglotticus by Kotby et al 8 who reported their “midlarynx” existence (i.e. at midpoint anteriorly).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The position of these fibers roughly corresponds to fibers identified as thryoepiglotticus by Kotby et al 8 who reported their “midlarynx” existence (i.e. at midpoint anteriorly).…”
Section: Discussionsupporting
confidence: 74%
“…As the posterior border of the laryngeal ventricle was approached, anterior coursing fibers of the ventricularis muscle, as observed by Kotby et al 8 appeared separate from the thyroartenoid and placed higher in the VF. These fiber bundles were typically irregular in cross-section and somewhat scattered within the VF tissue but lateral to the main mass of glandular tissue.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Others have noted that the superior portion of the thyroarytenoid muscle has much greater bulk in the human. 23 This study demonstrated that intermittent neuromuscular stimulation of the thyroarytenoid muscle could provide dynamic glottic adduction for airway protection. The Peterson electrode was well suited for implantation into the thyroarytenoid muscle; the 3-mm stimulating tip could be easily placed in the middle portion of the muscle without producing significant muscular destruction.…”
Section: Discussionmentioning
confidence: 99%